OVERALL ASSESSMENT OF DEFORMATION AND FORCE OF DIAPHRAGM WALL JOINTS DURING THE STAGES OF DEEP EXCAVATION CONSTRUCTION - Phuong Nguyen Tuan; Truong Dang Xuan; Tuan Nguyen; Hoa Tran Vu Van (International Journal for Computational Civil and Structural Engineering, 2024)
In the realm of geotechnical engineering, deep excavation projects face intricate challenges, especially concerning the stability of barrette walls, which are highly susceptible to deformation and stress at their joints. This study focuses on evaluating the deformation and force behavior of barrette wall joints at the position of greatest deformation. The Finite Element Method (FEM) is utilized to simulate the behavior of these structures under various load conditions. The Analysis of Variance (ANOVA) method is employed to statistically analyze the FEM data, assessing the impact of different factors on deformation and force distributions within the barrette wall joints. The specific objective of this study is to determine the statistical significance of the observed deformations and understand the influence of construction stages on joint integrity. This methodological synergy enhances the predictability of engineering assessments and ensures that design and construction decisions are grounded in solid empirical evidence. The study's findings emphasize the importance of precise monitoring and advanced predictive techniques to mitigate potential risks associated with deep excavations, particularly at critical joint locations. The results indicate that the deformation patterns are primarily influenced by the geometrical setup of the walls and the mechanical properties of the soils. The greatest deformations were typically observed where the wall joints experienced the highest bending moments and shear forces, conditions exacerbated by unfavorable soil mechanics and hydrostatic pressures. The clear and consistent increase in total displacement highlights the progressive destabilization of the wall as the excavation depth increases. By integrating ANOVA with FEM, this study contributes to enhancing safety and efficiency in deep excavation projects by ensuring that decisions are grounded in empirical evidence.